Nitrogen and Sulfur Fertilization Modulates the Yield, Essential Oil and Quality Traits of Wild Marigold (Tagetes minuta L.) in the Western Himalaya - Walia, Swati; Kumar, Rakesh (Frontiers in Plant Science, 2021)
Fertilization plays an irreplaceable role in raising crop yields; however, there are issues with unnecessary and blind use of chemical fertilizers, which raise the risk of contamination in the atmosphere. It is hypothesized that fertilization of nitrogen (N) and sulphur (S) will together improve the essential oil (EO) yield and composition of Tagetes minuta L. Thus, two years field experiment were carried out to evaluate the outcomes of N (0, 60, 90 and 120 kg ha-1) and S levels (0, 20, 40 and 60 kg ha-1) on T. minuta during 2018 and 2019. The growth, biomass, EO content and composition were influenced (P =0.05) by N and S fertilization. N at 120 kg ha-1 and S at 60 kg ha-1 registered higher biomass (183.89 and 178.90 q ha-1, respectively) and EO yield (102.09 and 88.60 kg ha-1, respectively), than control. Stomatal density reduced significantly with increase of N and S levels, however, density of oil glands substantially increased with S at 40 and 60 kg ha-1. The major component of EO (Z-β-ocimene) significantly increased with 120 kg N ha-1 (42.59 %) and 60 kg S ha-1 (42.35 %), respectively. Available nutrients in soil and plant tissues substantially increased with N and S fertilization upto 120 and 60 kg ha-1, respectively. The highest nutrient use efficiency traits were recorded at 60 kg N ha−1 and 20 kg S ha−1. It was concluded that 120 kg N ha-1 and 40 kg S ha-1 can be proposed for T. minuta as a result of agronomic responses, which serves as a sustainable means of cropping.